Body Condition Score as a Key Indicator of Milk Production in Dairy Cows in Tropical and Subtropical Regions - Febrianto Christi, Raden; Sudrajat, Ajat; Purnama, Itang (Bulletin of Applied Animal Research, 2026)
Body Condition Score (BCS) is a crucial indicator that reflects the body energy reserves of dairy cows and is closely linked to milk production performance, health, and reproductive efficiency. Environmental differences between tropical and subtropical regions, specifically temperature, humidity, and feed quality result in varying physiological responses regarding BCS and milk yield. This article aims to examine research findings related to the relationship between BCS and milk production in dairy cows across tropical and subtropical regions. The method used is a literature study of relevant national and international journals published within the last 15 years (2010–2025). The review results show that an optimal BCS at the start of lactation is positively correlated with high and stable milk production. However, in tropical regions, heat stress and limited feed quality often lead to a more severe decline in BCS, which negatively impacts milk production. Conversely, in subtropical regions, better feed and environmental management allow for more optimal BCS control. It is concluded that appropriate and region-specific BCS management is essential to maximize the production of a dairy cow. Keywords: BCS, Milk Production, Tropical, Subtropical.